PENGARUH KUALITAS LAYANAN, KESADARAN MEREK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI TOKOPEDIA PADA GENERASI MILENIAL SURABAYA - Nabilah Atika Rachman; Ronny, Ronny (JURNAL EKBIS, 2024)
The research objective is to analyze the impact of service quality on brand awareness, the influence of service quality on brand image, the effect of service quality on purchase decisions, the influence of brand awareness on decisions, and the influence of brand image on purchase decisions. The technical data analysis employed in this study is Partial Least Squares Structural Equation Modeling (PLS-SEM). The research findings reveal that service quality has a positive impact on brand awareness, service quality positively influences brand image, service quality positively affects purchase decisions, brand awareness positively affects purchase decisions, and brand image has a positive impact on purchase decisions.